Programas de integridade (compliance programs) e o direito na sociedade global: a concepção de um campo autônomo de regulação das nanotecnologias em usos militares - Wittmann, Cristian Ricardo (Universidade do Vale do Rio dos Sinos, 2016)
This thesis aim to study the regulatory function of compliance programs to the risk management of nanotechnology in its military uses in the context global society. Taking as initial step a pragmatic-systemic epistemological perspective and with the support of the constructivist method, has as main objective to analyze the possibilities and limits of the use of compliance programs for the regulation of nanotechnology in military use from a global and complex conception of society and of the Law System. While research problem tried to answer under which conditions the compliance programs could be considered a source of law in a global society with the emergence of military uses of nanotechnology. It is identified several limitations of the modern conception of law and society founded in the territory approach and the State exclusivity in the production and legal decision when the problems that come along with the contemporary. In this context it is showed the law as a separate and distinct field of State, with a polycontextural attribute, has its structure divided between center and periphery, recognizing new actors and legal contexts of production such as the Law produced within organizations. It is also understood the risk characteristic that marks the global society, particularly as a result of technological developments involving nanotechnologies and their military uses. It was observed that such changes provide scientific advances in products and processes while involve considerable uncertainty and risk of its consequences. Restrictions of risks in general nanotechnologies are presented together with those resulting from military uses, especially those provisions of International Humanitarian Law. Objectively the results presents the compliance programs as functional equivalents of the decision programs in the context of the teachings of Niklas Luhmann, Gunther Teubner and Leonel Rocha, presenting its characteristics, models and the possibility, within compatibility on the global and polycontextural of law produced. This line shows the possibilities with which the compliance programs integrate the Law System and thus be recognized as source of legal production in the organization’s perspective of a private, autonomous and voluntary basis in the context of the risks from nanotechnologies when military applications. It is confirmed, thus the hypothesis initially proposed when the research project phase of the possibility of understanding the compliance programs, when in compatibility with other global normative productions- including national and international orders, as law source applicable regarding the risks produced by systemic decisions of military uses of nanotechnology.
Keywords: Programas de integridade; Sociedade de risco global; Nanotecnologia em uso militar; Constitucionalismo global; Compliance programs; Global risk society; Military use of nanotechnology; Global constitutionalism; ACCNPQ::Ciências Sociais Aplicadas::Direito